THE USE OF FOOTBALL DIPLOMACY FOR SOCIO-POLITICAL AND CONFLICT RESOLUTION IN AFRICA: THE CONFEDERATION OF AFRICAN FOOTBALL HISTORICAL PERSPECTIVE (LAPAI JOURNAL OF NIGERIA HISTORY, 2023)
This study reviews football's role as a diplomatic tool for achieving socio-political development and conflict resolution in Africa. Specifically, the Paper extensively reviews and assesses the contributions of the Confederation of African Organized Football (CAF) tournament to African development and conflict resolution. The paper identifies that football significantly impacts on politics, diplomacy, conflict resolution, and even peacebuilding. Organized tournaments have been found to have been used by African countries to express both pleasure and displeasure through participation and boycott of the tournament. CAF organized football tournaments have also been used to punish a country by banning from taking part and fines. It was also highlighted that there has been a remarkable decline in violent conflict across Africa in the past decade. However, this has not always been equated to peace achieved through the roles played by football stars as peace ambassadors. The paper recommends football as a tool for diplomatic relations. Football has also been seen to be one of the greatest tools in promoting bilateral diplomatic relations among the nations in Africa and globally. Football diplomacy transcends cultural differences and creates opportunities for alternate avenues for overcoming hostilities, official dialogue and inter-group relations, uniting separate nations through a love of football